Economic and Social Survey of Asia and the Pacific 2013 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2013)
This document provides a review of the region’s performance in 2012 and its outlook in 2013, as it recovers from the global economic crisis and assesses the region’s policy response to remaining and emerging vulnerabilities. Areas of economic and social policy analysed include growth, inflation, trade and investment, financial markets, employment, migration and remittances. Key challenges ahead are addressed and policy responses recommended for countries in order to sustain their development. The document also addresses a thematic issue, discussing the current approach of macroeconomic policy making and critically assessing whether it has served development adequately.